Peripheral Nerve Injuries in Laparoscopic and Open Thoracoabdominal Surgeries: A Systematic Review and Meta-Analysis - Nguyen, John D.; Chen, Alec J.; Snee, Isabel; Khong, Jeffrey; Poisler, Mark A.; Elhelali, Ala; Tuffaha, Sami H.; Dellon, Arnold Lee (Journal of Reconstructive Microsurgery, 2025)
Following open thoracoabdominal surgery, patients are at risk of chronic pain due to unintentional peripheral nerve injury (PNI), such as nerve transection, compression, or stretching of peripheral nerves. While laparoscopic surgery is minimally invasive, the incidence of subsequent PNI from laparoscopic surgery remains unknown.PubMed, Embase, Web of Science, and Scopus databases were searched for peer-reviewed literature discussing nerve injuries following open or laparoscopic thoracoabdominal surgeries.From 1,580 unique citations, 28 articles (n = 871 patients) qualified for inclusion. There were 555 (63.7%) males and 316 (36.3%) females. The mean age was 54.5 ± 9.6 years, ranging from 18 to 92. Following 451 open thoracoabdominal surgeries, there were 214 nerve injuries (47.5%). Following 420 laparoscopic thoracoabdominal surgeries, there were 22 nerve injuries (5.2%). Laparoscopic surgery had statistically significantly lower PNI (p < 0.0001) than open procedures. These procedures caused 236 reported cases of PNI, which included neuromas (50.4%), nerve enlargement (37.3%), nerve transection (8.5%), nerve entrapment (2.5%), perineural inflammation (2.2%), and nerve crush injury (0.4%). Of patients with PNI, surgery was performed on 170 (72.0%) patients, and nonsurgical treatments were given in 64 (27.1%) patients. The surgical interventions for PNI included neurectomy (78.8%), neuroma excision (19.4%), and scar excision (1.8%).A laparoscopic approach, versus a surgical open approach to treat thoracoabdominal surgical problems, has decreased the risk of inadvertent nerve injuries. The wide variation in the description of the types of injuries is indicative of the generally poorly understood nature of PNI, indicating an opportunity for greater emphasis on the diagnosis and treatment of this problem.
Keywords: neuroma; PNI; laparoscopy; minimally invasive surgical procedures